Wind tunnel investigation of the aerodynamic response of two 15 MW floating wind turbines - A. Fontanella; A. Facchinetti; S. Di Carlo; M. Belloli (Wind Energy Science, 2022)
The aerodynamics of floating turbines is complicated by large motions which are permitted by the floating foundation, and the interaction between turbine, wind, and wake is not yet fully understood. The object of this paper is a wind tunnel campaign finalized at characterizing the aerodynamic response of a 1:100 scale model of the IEA 15 MW subjected to imposed platform motion. The turbine aerodynamic response is studied focusing on thrust force, torque, and wake at 2.3D downwind the rotor. Harmonic motion is imposed in the surge, sway, roll, pitch, and yaw directions with several frequencies and amplitudes, which are selected to be representative of the two 15 MW floating turbines developed within the COREWIND project. Thrust and torque show large-amplitude oscillations with surge and pitch motion, the main effect of which is an apparent wind speed; oscillations in thrust and torque are negligible with the other motions, the main effect of which is to alter the wind direction. The thrust and torque response measured in the experiment is compared with predictions of a quasi-steady model, often used for control-related tasks. The agreement is good in the case of low-frequency surge motion, but some differences are seen in the pitch case. The quasi-steady model is not predictive for the response to wave-frequency motion, where blade unsteadiness may take place. Wake was measured imposing motion in five directions with frequency equal to the wave frequency. The axial speed is slightly lower with motion compared to the fixed case. The turbulence kinetic energy is slightly lower too. Wave-frequency motion seems to produce a more stable and lower flow mixing.